Evaluation of efficacy of preservatives associated with Achillea millefolium L. extract against Bacillus subtilis - Salvagnini, Luiz E.; Migliato, Ketylin F. [UNESP]; Isaac, Vera Lucia Borges [UNESP]; Correa, Marcos Antonio [UNESP]; Salgado, Hérida Regina Nunes [UNESP]; Pietro, Rosemeire C.L.R. [UNESP] (Sociedade Brasileira de Microbiologia, 2006)
A eficácia antimicrobiana de conservantes empregados em formulações cosméticas foi avaliada usando Phenova® e Imidazolinidil uréia que inibiram o crescimento de Bacillus subtilis no extrato de Achillea millefolium L. e Nipagin®/ Nipasol® 0,2% em propilenoglicol não apresentaram efeito microbicida.

The antimicrobial efficacy of three preservatives used in cosmetic formulations was evaluated. Phenova® and imidazolidinyl urea inhibited the growth of Bacillus subtilis when added to leaf extract of Achillea millefolium L., whereas 0.2% Nipagin®/ Nipasol® in propylene glycol did not.
Avaliação da eficácia de conservantes associados a extrato de Achillea millefolium L. contra Bacillus subtilis
Keywords: Achillea millefolium L.; conservantes; atividade antibacteriana; Bacillus subtilis; Achillea millefolium L.; preservatives; antibacterial activity; Bacillus subtilis